Refractory Vestibulo-Auditory Symptoms in Early-Onset Meniere’s Disease with Coexisting Sinonasal Inflammation: A Case Report (Bangladesh Journal of Medicine, 2026)
Meniere’s disease is a chronic disorder of the inner ear characterized by episodic vertigo, fluctuating sensorineural hearing loss, tinnitus, and aural fullness. The condition predominantly affects middle-aged adults; early-onset presentations are rare and often misdiagnosed, particularly when sinonasal pathology coexists. We report the case of an 18-year-old male presenting with persistent bilateral tinnitus, progressive hearing loss, recurrent vertigo attacks, nausea, imbalance, headache, facial pain, and ear discomfort for more than one year. Despite prolonged medical therapy including betahistine, cinnarizine, prochlorperazine, clonazepam, analgesics, and multivitamin supplementation, symptoms persisted and significantly impaired quality of life. Computed tomography of the paranasal sinuses revealed mucosal thickening and partial opacification of the maxillary and ethmoid sinuses, suggestive of chronic sinusitis with possible Eustachian tube dysfunction. Clinical findings were consistent with early-onset Meniere’s disease. Given poor response to pharmacological therapy, the patient was advised bilateral myringotomy with ventilation tube placement, followed by intratympanic steroid administration to reduce inner ear inflammation and stabilize vestibular symptoms. This case highlights the diagnostic complexity of early-onset Meniere’s disease when associated with chronic sinonasal inflammation. Early multidisciplinary evaluation and targeted intratympanic therapy may improve symptom control and prevent long-term auditory-vestibular disability.Bangladesh J Medicine 2026; 37(2): 156-160